Prevalence and severity of premenstrual symptoms among female academic staff of University of Jaffna - Kamalarupan, L.; Sivapalan, K.; Fernando, M.U.R.N. (University of Jaffna, 2022)
Premenstrual symptoms are recurrent, cyclic disorder in women at reproductive age. There are wide spectrums of physical and emotional symptoms that occur regularly during one to two weeks before the start of each menstrual cycle. The study aimed to assess the prevalence and severity of premenstrual symptoms among female academic staff of the University of Jaffna. The institutional based descriptive cross-sectional study was carried out among female academic staffs after receiving ethical clearance from the Ethical Review Committee, Faculty of Medicine, University of Jaffna. Data were collected using a self-administered questionnaire via google forms in sinhala, tamil and english and analysed by SPSS version 25. Among 245 study participants, only 207 participants were eligible for the assessment of premenstrual symptoms, since they were experiencing at least one cycle of menstruation within the last three months. Among them, 93.2% (n=193) reported at least one premenstrual symptom, while 6.8% (n=14) did not experience any of the premenstrual symptoms. The most “severe” symptoms reported by the participants during their premenstrual days were irritability or getting angry for small things (24.2%), mood swings (23.2%), feeling sad (19.3%), extreme tiredness (16.9%) and heaviness of breast (15.9%). The most common “moderate” symptom was bloating (21.7%). The least reported “mild” premenstrual symptom was facial puffiness (9.2%). Premenstrual symptoms were a common problem among female academic staffs of University of Jaffna (93.2%). For the majority of participants, emotional symptoms were more severe than the physical symptoms during their premenstrual days. It is recommended to increase awareness among the female academic staffs and colleagues about premenstrual symptoms.
Keywords: Premenstrual symptoms; Prevalence; Severity; Jaffna